PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 67 PEKANBARU - Manalu, Clara Anastasia Feronika; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is caused by the low of science’s learning outcome of the fourth grade students at SDN 67 Pekanbaru in science subject. Based on the minimum mastery criteria (KKM), which set at school is 75, from 28 students of the fourth grade who reach KKM are 12 students (42,86 %) and the students who do not reach KKM are 16 students (57,14 %) with an average score 66,96. The objective of this research it to increase the science’s learning outcome of the fourth grade students at SDN 67 Pekanbaru by the application of inquiry learning model. Inquiry learning model is a learning model that emphasize students critical thinking and can answer a question or problem by themselves. This research was conducted in two cycles, one cycle twice teaching. The result of data analysis shows teacher and students activities, learning outcome, and mastery of learning outcomes. This research present the learning outcomes which is obtained from daily test result before action with an average score 66,96 increase to 71,07 in cycle I , and increase more become 78,21 in cycle II. Teacher activities in cycle I first meeting is 62,5 %, second meeting is 83,33 %, with an average score 72,91 in average level, in cycle II first meeting is 87,5 %, second meeting is 91,67 %, with an average score 89,58% in excellent level. Students activities in cycle I first meeting is 62,5 %, in second meeting is 79,16 %, with an average score 70,83 % in average level. In cycle II first meeting 83,33 % in second meeting 91,67 %, with an average score 87,5 % in excellent level. Based on the result analysis it can be concluded that the application of inquiry model learning can increase the science’s learning outcome of the fourth grade student at SDN 67 Pekanbaru.Kay words: Inquiry learning model, science’s learning outcomes.